Enercy Efficient Virtual Network Embedding in Data Center Optical Networks - Jia-qi NIE (Guangtongxin yanjiu, 2022)
To solve the energy consumption problem in Data Center Optical Networks (DCONs), an Energy Efficient Embedding algorithm based on Matching Network Resources (3E-MNR) scheme is proposed. The algorithm adopts coordinated virtual network embedding based on the concept of embedding matching resources. In the process of virtual embedding, the resource constraints of nodes and links are taken into account at the same time. The algorithm selects the appropriate modulation format and location of regenerator and Optical Transponder (OTP) according to the link distance. The network resource with the lowest energy consumption is chosen to complete the embedding. Experimental results show that the proposed algorithm can reduce the total energy consumption and the OTP energy consumption compared with the two baseline algorithms. The performance is better when the number of virtual requests is high. The network blocking rate can be reduced on the basis of achieving the trade-off of running time.